(3GdfU GdJTQjYj Hjf GdJaSjQ hGdJWHjb hCKQg aj JMbjb GdCef GdacQj hGdSdGe GdGLJeGYj fMh fehPL eYQaj ESdGej (B/s - (3LYaQ, gGfj ceGd eMeOs ((3GdLjRI, eUQ (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2022)
(3JHQR CgejI GdehVhY aj chfg(B-(3MSH Xfj(B-(3bQGAI ZGFHI JJMQc eY GdfUhU hQhMgG, hJSJNOegG hYGAG ChSY ef HfjJgG GddZhjI, eSJgOaI HgG MVhQ GdJTQjY CeQG hfgjG aj cd LhGfH GdMjGI ; MjK dG JNdh fGRdI Yf Mce, hdG jJSQH hGbY egeG cGfJ LRFjGJg dG eJfGgjI, hef Ke MGhdJ HjGf GdJCda Hjf JaSjQ GdfU hJWHjbg, Ch GdJSGcf Hjf GdEjeGf hebJVjGJ GdReGf, hCKQ Pdc aj JMbjb GdCef GdacQj hGdSdGe GdGLJeGYj ; HhGSWI CUhd Gdabg, PGc GdPj jeKd CaVd efgL GNJQYJg GdYbhd GdESdGejI ddJYGed eY fUhU GdhMj GdEdgj, hgh efgL NGdO; dCfg jSJeO jfHhYg heGOJg ef fUhU GdhMj hdZJg, hgh GdCeQ GdPj cad dg GdHbGA hVef dg GdfbGA, hdPG hUa HCfg (B: (3Yde (B"(3jXgQ YHbQjI GdYbhd GdeHOYI GdJj YQaJ cja JUfY GdefgL GdUMjM dEOQGc GdZGjI(B"(3, hdCgejJg GdJTQjYjI aj JaSjQ GdfUhU GdTQYjI hGdhVYjI JQLe Edi GddZI GdEfLdjRjI, hZOG jOQS Gdjhe aj GdLGeYGJ GdZQHjI ; cLGeYI gGQaGQO aj CejQcG(B.s
(3HHdjhLQGajI (B: (3UaMI (B197-203.s
Keywords: (3GdbQBfs -- (3JaGSjQ MOjKIs; (3GdESdGe hGdZRh GdacQjs; (3GdESdGe hGdEUdGM GdGLJeGYjs; (3GdTQjYI GdESdGejIs